Optimization of cornmeal agar culture for yeast microscopic morphology identification test - Noor, Nor Aida Kasma Mohd (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2004)
Optimization of Cornmeal-Tween 80 (CMT) agar culture for yeast microscopic morphology identification test was done at varying pH and incubation temperature. A series of experiment were undertaken to optimize the medium by morphology identification of Candida albicans, Candida glabrata and Candida tropical is. The result obtained from this study showed that the optimum pH is 5 for Candida albicans and Candida tropical is, whereas pH 5 to 7 for Candida glabrata. The optimum temperature is 24°C to 30°C. From this study, the selective feature for identification of Candida albicans is the formation of clamydospore at 30°C and pH 5. The species is different form another species when the culture was inoculated at pH 10 at 37°C and 45°C. There was no growth observed under these conditions. For Candida tropical is, the special selective feature is that the species can survive at incubation temperature of 45°C compared to other species. Selective feature for Candida glabrata was not observed under the optimized growth conditions.